6S RNA: recent answers – future questions. Issue 4 (7th January 2014) - Steuten, Benedikt; Schneider, Sabine; Wagner, Rolf
Summary 6S RNA is a non‐coding RNA, found in almost all phylogenetic branches of bacteria. Through its conserved secondary structure, resembling open DNA promoters, it binds to RNA polymerase and interferes with transcription at many promoters. That way, it functions as transcriptional regulator facilitating adaptation to stationary phase conditions. Strikingly, 6S RNA acts as template for the synthesis of small RNAs (pRNA), which trigger the disintegration of the inhibitory RNA polymerase‐6S RNA complex releasing 6S RNA‐dependent repression. The regulatory implications of 6S RNAs vary among different bacterial species depending on the lifestyle and specific growth conditions that they have to face. The influence of 6S RNA can be seen on many different processes including stationary growth, sporulation, light adaptation or intracellular growth of pathogenic bacteria. Recent structural and functional studies have yielded details of the interaction between E. coli 6S RNA and RNA polymerase. Genome‐wide transcriptome analyses provided insight into the functional diversity of 6S RNAs. Moreover, the mechanism and physiological consequences of pRNA synthesis have been explored in several systems. A major function of 6S RNA as a guardian regulating the economic use of cellular resources under limiting conditions and stress emerges as a common perception from numerous recent studies.